2017
DOI: 10.1113/jp273473
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that 5‐HT stimulates intracellular Ca2+ signalling and activates pannexin‐1 currents in type II cells of the rat carotid body

Abstract: Carotid body (CB) chemoreceptor (type I) cells can synthesize and release 5-HT and increased autocrine-paracrine 5-HT receptor signalling contributes to sensory long-term facilitation during chronic intermittent hypoxia (CIH). However, recent studies suggest that adjacent glial-like type II cells can respond to CB paracrine signals by elevating intracellular calcium (Δ[Ca ] ) and activating carbenoxolone-sensitive, ATP-permeable, pannexin (Panx)-1-like channels. In the present study, using dissociated rat CB c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 43 publications
(127 reference statements)
5
44
0
Order By: Relevance
“…Similar to previous studies (Murali et al, 2017), 5-HT (5 M) caused a delayed activation of an inward Panx-1-like current at a holding potential of −60 mV in several type II cells, as exemplified in Figure 1a.…”
Section: Role Of Src Family Kinase In the Activation Of The Pannexin-supporting
confidence: 88%
See 4 more Smart Citations
“…Similar to previous studies (Murali et al, 2017), 5-HT (5 M) caused a delayed activation of an inward Panx-1-like current at a holding potential of −60 mV in several type II cells, as exemplified in Figure 1a.…”
Section: Role Of Src Family Kinase In the Activation Of The Pannexin-supporting
confidence: 88%
“…Previous studies from this laboratory demonstrated that 5-HT acts on ketanserin-sensitive 5-HT2Rs on type II cells leading to an increase in intracellular Ca 2+ that appears necessary for the activation of ATP-permeable Panx-1 channels (Murali et al, 2017). SFK, PKA and PKC, in the 5-HT-5HT2R signalling pathway in type II glial cells of the rat CB.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations